Self-Identification and Racial Preference in Urban and Rural Primary School Children from South Sumatra, Indonesia (Beacon: International Journal of Education and Social Studies, 2026)
This study examines self-identification and racial preference among primary school children in urban and rural areas of South Sumatra, Indonesia. Using a qualitative case study approach, data were collected from 24 students through an adapted Doll Test to explore early perceptions of skin color, identity, and social evaluation. The findings reveal that most children tend to associate lighter skin tones with positive attributes such as beauty, goodness, and higher socio-economic status, while darker skin tones are more frequently linked to negative stereotypes. However, some participants demonstrated more inclusive and flexible perspectives, indicating variability in early racial attitudes. Interestingly, self-identification did not always align with preference, as many children still identified with darker-skinned dolls despite favoring lighter skin in other judgments. Limited exposure to diverse representations was also found to influence children’s perceptions. The study highlights the role of social environment, cultural narratives, and representation in shaping early identity formation and bias. It emphasizes the importance of inclusive education and diverse learning materials to foster tolerance and reduce racial stereotyping in early childhood development.